Ferroelectric (Ba,Sr)1-xLaxTiO3 thin films electron field emission applications - Lu, Hua (2008)
In this thesis, ferroelectric (Ba0.65Sr0.35)TiO3 (BST) and (Ba0.65Sr0.35)1-xLaxTiO3+y (BSLT with ) thin films have been fabricated on silicon tip arrays using the sol-gel technique for potential field emission applications. The ferroelectric film coated Si tip arrays show substantial improvement of field emission compared to bare Si tip arrays. The threshold electric field could be lowered from 36 V/?m for bare Si tip arrays to about 15 V/?m for 30-nm-thick BSLT ( ) coated Si tip arrays. The field emission properties are highly correlated to the annealing temperature and thickness of BST-coated arrays, and to the La concentration for BSLT-coated arrays. Systematic studies of the microstructure and electronic structure of ferroelectric thin films have been carried out to understand field emission mechanism. It is found that the enhancement of field emission of the coated Si arrays results from improved perovskite structure in the surface region, suppressed interfacial reaction, and up-moved Fermi level of the ferroelectric thin film coatings.